Odpowiedzi

2009-12-03T15:35:52+01:00
A) (x+1)²=x²+2x+1
b) (1+x)²=1+2x+x²
c) (x+a)²=x²+2ax+a²
d) (x+1)²=x²+2x+1
e) (2x+2)²=4x²+4+8x²
f) (½x+1)²=1/4x²+x+1
g) (x+0,5)²=x²+x+0,25
h) (-x+1)²= x²-2x+1

2
a) (3-x)²= 9-6x+x²
b) (x-7y)²=x²-14xy+49y²
c) (2x-2)²=4x²-8x+4
d) (x-0,1)²=x²-0,2x+0,01
e) (0,5x-1)²=0,25x-x+1
g) (4x-0,5)²=16x²-4x+0,25

1 5 1
2009-12-03T15:36:26+01:00
1.
a) x²+1
b) 1+x²
c)x²+a²
d)x²+1
e)4x+4
f)¼x+1
g)x²+0,25
h)-x²+1
2.
a)9-x²
b)x²+49y
c)4x-4
d)x²-0,1
e)0,25-1
f)16x-0,25
1 1 1
2009-12-03T15:54:05+01:00
1wzór(a+b)²=a²+2ab+b²
a) (x+1)²=x²+2*x*1+1²=x²+2x+1
b) (1+x)²=1²+2*1*x+x²=1²+2x+x²=1+2x+x²
c) (x+a)²=x²+2*x*a+a²=X²+2xa+a²
d) (x+1)²=x²+2*x*1+1²=x²+2x+1
e) (2x+2)²=4x²+2*2x*2+4=4x²+8x+4
f) (½x+1)²=¹/₄x+2*¹/₂x*1+1=¹/₄x+x+1
g) (x+0,5)²=x²+x+0,25
h) (-x+1)²=x²-2x+1

2wzór(a-b)²=a²-2ab+b²
a) (3-x)²=9-2*3*x+x²=9-6x+x²
b) (x-7y)²=x²-2*x*7y+49y²=x²-14xy+49y²
c) (2x-2)²=4x²-2*2x*2+4=4x²-8x+4
d) (x-0,1)²=x²-2*x*0,1+0,01=x²-0,2x+0,01
e) (0,5x-1)²=0,25x²-2*0,5x*1+1=0,25x²-x+1
g) (4x-0,5)²=16x²-2*4x*0,5+0,25=16x²-4x+0,25